MOTIVASI WISATAWAN BERKUNJUNG KE OBJEK WISATA ASIA HERITAGE DI KOTA PEKANBARU - Wilfidandi, Yanda; Yusrizal, Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study aims to identify the motivations of tourists visiting the Asia Heritage tourist attraction in Pekanbaru City, Riau Province. The research employs a quantitative descriptive approach. Data were collected through questionnaires distributed to 100 respondents selected using an accidental sampling technique. The variables examined consist of push factors and pull factors, and the data were analyzed using descriptive frequency analysis. The findings indicate that the main tourist motivations stem from internal factors such as the desire for relaxation, recreation, and strengthening family bonds. Additionally, external factors such as the thematic Asian tourism concept, complete facilities, and the abundance of attractive photo spots also contribute to tourists' interest in visiting. Thus, the combination of personal motivation and destination appeal serves as the key determinant in tourists' decisions to choose Asia Heritage as a travel destination. These findings are expected to provide input for destination managers in developing promotional strategies and sustainable tourism management. Keywords: Motivation, Tourists, Asia Heritage, Push Factors, Pull Factors